Reservoir and vector evolutionary pressures shaped the adaptation of Borrelia - Estrada-Peña, Agustín; Álvarez-Jarreta, Jorge; Cabezas-Cruz, Alejandro (Infection, genetics and evolution, 2018)
The life cycle of spirochetes of the genus Borrelia includes complex networks of vertebrates and ticks. The tripartite association of Borrelia-vertebrate-tick has proved ecologically successful for these bacteria, which have become some of the most prominent tick-borne pathogens in the northern hemisphere. To keep evolutionary pace with its double-host life history, Borrelia must adapt to the evolutionary pressures exerted by both sets of hosts. In this review, we attempt to reconcile functional, phylogenetic, and ecological perspectives to propose a coherent scenario of Borrelia evolution. Available empirical information supports that the association of Borrelia with ticks is very old. The major split between the tick families Argasidae-Ixodidae (dated some 230-290 Mya) resulted in most relapsing fever (Rf) species being restricted to Argasidae and few associated with Ixodidae. A further key event produced the diversification of the Lyme borreliosis (Lb) species: the radiation of ticks of the genus Ixodes from the primitive stock of Ixodidae (around 217 Mya). The ecological interactions of Borrelia demonstrate that Argasidae-transmitted Rf species remain restricted to small niches of one tick species and few vertebrates. The evolutionary pressures on this group are consequently low, and speciation processes seem to be driven by geographical isolation. In contrast to Rf, Lb species circulate in nested networks of dozens of tick species and hundreds of vertebrate species. This greater variety confers a remarkably variable pool of evolutionary pressures, resulting in large speciation of the Lb group, where different species adapt to circulate through different groups of vertebrates. Available data, based on ospA and multilocus sequence typing (including eight concatenated in-house genes) phylogenetic trees, suggest that ticks could constitute a secondary bottleneck that contributes to Lb specialization. Both sets of adaptive pressures contribute to the resilience of highly adaptable meta-populations of bacteria.
Keywords: Adaptation, Biological; Ticks; infekce přenášené vektorem; Tick-Borrelia-reservoir interaction; Disease Reservoirs; Humans; Borrelia; Host-Pathogen Interactions; interakce hostitele a patogenu; Lyme Disease; lymeská nemoc; zdroje nemoci; Biological Evolution; biologická adaptace; lidé; zvířata; Disease Vectors; klíšťata; biologická evoluce; Animals; Evolutionary pressure; selekce (genetika); Selection, Genetic